IFRS Based Zakat Reporting: Adoption Rational Western Method Into Institutional Accountability - Pamuncak, Mohammad Bintang; Possumah, Bayu Taufiq; Abdul Halim, Zairihan (IKONOMIKA, 2018)
ABSTRACTThis study aims to evaluate the characteristics of zakat institution and proposes the adoption of International Financial Reporting Standard (IFRS) since it has developed and provides various product i.e zakat for productive purpose. This is important, considering that one of the measurement of accountability and transparency of an institution is providing brief financial report towards its beneficaries. Thereby, this study found that practically zakat institution is simillar to the SMEs, and there are 11 strandard of IFRS for SMEs that could be applicable to zakat institutionto achieve accountability and transparency. However, this study is preliminary study that proposes a conceptual frameworkwhich limited to the sharia compliance of IFRS that could be applicable to zakat Institution. Keywords: IFRS for SMEs, SMEs Criteria, Zakat InstitutionJEL Classification: